Behind the shower curtain: Seven poems on aging and body cleaning - Karaca Şalgamcıoğlu, Berrak; Er, Özlem (Sage Publications Inc, 2018)
Bathroom is one of the first places that older adults face with challenge and fear. Difficulty or dependence in body-cleaning affect older adults' daily lives dramatically. Despite the consequences associated with disability in body-cleaning, little is known about older adults' experiences on it. One reason for this lack of knowledge may be that body-cleaning is a private activity and a difficult task to explore. This article will present seven poems that are results of a research study where older women were asked to narrate of their own body-cleaning experience to a tape recorder while they were performing the task.
WOS: 000439628100005
Keywords: Aging; Body Cleaning; Bathroom; Poetic Representation; Design